The Methyltransferase-Like Domain of Chikungunya Virus nsP2 Inhibits the Interferon Response by Promoting the Nuclear Export of STAT1 - Göertz, Giel P; McNally, Kristin L; Robertson, Shelly J; Best, Sonja M; Pijlman, Gorben P; Fros, Jelke J (Journal of virology, 2018)
Chikungunya virus (CHIKV) is a mosquito-borne alphavirus that has evolved effective mechanisms to counteract the type I interferon (IFN) response. Upon recognition of the virus, cells secrete IFNs, which signal through transmembrane receptors (IFNAR) to phosphorylate STAT proteins (pSTAT). pSTAT dimers are transported into the nucleus by importin-α5 and activate the transcription of IFN-stimulated genes (ISGs), increasing cellular resistance to infection. Subsequently, STAT proteins are shuttled back into the cytoplasm by the exportin CRM1. CHIKV nonstructural protein 2 (nsP2) reduces ISG expression by inhibiting general host cell transcription and by specifically reducing the levels of nuclear pSTAT1 via an unknown mechanism. To systematically examine where nsP2 acts within the JAK/STAT signaling cascade, we used two well-characterized mutants of nsP2, P718S and KR649AA. Both mutations abrogate nsP2's ability to shut off host transcription, but only the KR649AA mutant localizes exclusively to the cytoplasm and no longer specifically inhibits JAK/STAT signaling. These mutant nsP2 proteins did not differentially affect IFNAR expression levels or STAT1 phosphorylation in response to IFNs. Coimmunoprecipitation experiments showed that in the presence of nsP2, STAT1 still effectively bound importin-α5. Chemically blocking CRM1-mediated nuclear export in the presence of nsP2 additionally showed that nuclear translocation of STAT1 is not affected by nsP2. nsP2 putatively has five domains. Redirecting the nsP2 KR649AA mutant or just nsP2's C-terminal methyltransferase-like domain into the nucleus strongly reduced nuclear pSTAT in response to IFN stimulation. This demonstrates that the C-terminal domain of nuclear nsP2 specifically inhibits the IFN response by promoting the nuclear export of STAT1. Chikungunya virus is an emerging pathogen associated with large outbreaks on the African, Asian, European, and both American continents. In most patients, infection results in high fever, rash, and incapacitating (chronic) arthralgia. CHIKV effectively inhibits the first line of defense, the innate immune response. As a result, stimulation of the innate immune response with interferons (IFNs) is ineffective as a treatment for CHIKV disease. The IFN response requires an intact downstream signaling cascade called the JAK/STAT signaling pathway, which is effectively inhibited by CHIKV nonstructural protein 2 (nsP2) via an unknown mechanism. The research described here specifies where in the JAK/STAT signaling cascade the IFN response is inhibited and which protein domain of nsP2 is responsible for IFN inhibition. The results illuminate new aspects of antiviral defense and CHIKV counterdefense strategies and will direct the search for novel antiviral compounds.